The Role of Psychological Capital and Adversity Quotient in predicting Career Adaptability Among Vocational High School Students - Ika Mujiani; Maharani Tyas Budi Hapsari (Jurnal Psikologi Teori dan Terapan, 2026)
Background: Career adaptability is a crucial psychosocial resource for vocational high school students transitioning from school to work. Psychological Capital (PsyCap) and Adversity Quotient (AQ) are internal strengths assumed to support adaptive career development. Objective: This study examined the predictive roles of PsyCap and AQ in career adaptability among students at SMK Negeri 1 Miri. Method: A quantitative correlational design using multiple linear regression was applied. The sample consisted of 169 twelfth-grade students selected through cluster random sampling. Data were collected using 1–5 Likert-scale questionnaires measuring PsyCap, AQ, and career adaptability. Classical assumption tests were conducted prior to analysis. Results: Both PsyCap and AQ significantly predicted career adaptability. PsyCap demonstrated a stronger predictive contribution (β = 0.412, p < 0.001) than AQ (β = 0.311, p < 0.001). Simultaneously, the two variables explained 32.7% of the variance in career adaptability (R² = 0.327), indicating a moderate predictive model. Conclusion: The findings emphasize the importance of proactive psychological resources in strengthening vocational students’ readiness for school-to-work transitions. Integrating PsyCap and AQ development into vocational career guidance programs may enhance students’ adaptive capacity and transition preparedness. Abstrak Latar Belakang: Adaptabilitas karier merupakan sumber daya psikososial penting bagi siswa sekolah menengah kejuruan dalam menghadapi transisi sekolah ke dunia kerja. Psychological Capital (PsyCap) dan Adversity Quotient (AQ) dipandang sebagai kekuatan psikologis internal yang mendukung perkembangan karier adaptif. Tujuan: Penelitian ini bertujuan menganalisis peran prediktif PsyCap dan AQ terhadap adaptabilitas karir siswa SMK Negeri 1 Miri. Metode: Penelitian menggunakan pendekatan kuantitatif korelasional dengan analisis regresi linier berganda. Sampel terdiri dari 169 siswa kelas XII yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner skala Likert 1–5 yang mengukur PsyCap, AQ, dan adaptabilitas karir. Uji asumsi klasik dilakukan sebelum analisis utama. Hasil: PsyCap dan AQ secara signifikan memprediksi adaptabilitas karir. PsyCap menunjukkan kontribusi prediktif yang lebih kuat (β = 0.412, p < 0.001) dibandingkan AQ (β = 0.311, p < 0.001). Secara simultan, kedua variabel menjelaskan 32,7% varians adaptabilitas karir (R² = 0.327), menunjukkan model prediksi yang moderat. Kesimpulan: Temuan menegaskan pentingnya sumber daya psikologis proaktif dalam meningkatkan kesiapan transisi sekolah-ke-dunia kerja pada siswa vokasi. Integrasi pengembangan PsyCap dan AQ dalam program bimbingan karir SMK berpotensi memperkuat kapasitas adaptif siswa.